2021
DOI: 10.3390/en14164855
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation and Combustion of a Layer of Methane Hydrate Powder: Ways to Increase the Efficiency of Combustion and Degassing

Abstract: The interest in natural gas hydrates is due both to huge natural reserves and to the strengthened role of environmentally friendly energy sources conditioned by the deterioration of the global environmental situation. The combustion efficiency increase is associated with the development of understanding of both the processes of dissociation and combustion of gas hydrates. To date, the problems of dissociation and combustion have, as a rule, been considered separately, despite their close interrelation. Usually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…where ∆T is the mean difference between the maximum gas temperature in the boundary layer and the average surface temperature of the layer, V e f is the effective gas rate in the dynamic boundary layer, L is the length of the site with the hydrate, and Pr is the Prandtl number. When describing the gas hydrate dissociation rate, it is important to take into consideration not only the kinetics of dissociation but also the heat and mass transfer inside porous solids [111]. Hassanpouryouzband et al [112] presented the kinetics of gas hydrate formation and dissociation.…”
Section: Formation and Dissociation Of Gas Hydratesmentioning
confidence: 99%
See 3 more Smart Citations
“…where ∆T is the mean difference between the maximum gas temperature in the boundary layer and the average surface temperature of the layer, V e f is the effective gas rate in the dynamic boundary layer, L is the length of the site with the hydrate, and Pr is the Prandtl number. When describing the gas hydrate dissociation rate, it is important to take into consideration not only the kinetics of dissociation but also the heat and mass transfer inside porous solids [111]. Hassanpouryouzband et al [112] presented the kinetics of gas hydrate formation and dissociation.…”
Section: Formation and Dissociation Of Gas Hydratesmentioning
confidence: 99%
“…The maximum dissociation rate of gas hydrates is achieved using induction heating [59]. To estimate the effect of gas hydrate geometry on the ignition characteristics, researchers have experimentally studied the combustion behavior of powder [56,58,111], cylindrical [66], and spherical [62,63,69,70] hydrate forms. Their findings revealed that gas hydrates in powder form are ignited more easily and burn out more completely.…”
Section: Combustion Behavior Of Gas Hydratementioning
confidence: 99%
See 2 more Smart Citations
“…development of gas hydrate deposits, are presented in [13][14][15][16][17]. Modeling of gorenje hydrate methane with account of the non-stationary process of its dissociation in the powder layer is presented, in particular, in [18].…”
Section: Introductionmentioning
confidence: 99%